MARIO TEGUH’S RHETORICAL STYLE THROUGH YOUTUBE AND INSTAGRAM CHANNELS - Andriani, Kiki; Malik Ibrahim (INJECT (Interdisciplinary Journal of Communication), 2023)
This research aims to analyze Mario Teguh’s rhetorical style through YouTube and Instagram. The benefits of the research can provide a reference for motivators to use rhetorical style in public speaking. This research uses qualitative research with a discourse analysis approach. Data collection techniques using observation and documentation and validity techniques using source triangulation. Based on word choice, Mario Teguh uses official, unofficial, and conversational styles. Based on tone, he uses simple, medium, noble and powerful styles. Based on sentence structure using climax, anti-climax, parallelism, antithesis, and repetition. Based on voice style Mario Teguh uses a slow rate, pauses with the word "em", pitch with high and low tones. On the volume Mario Teguh shows soft and loud. Based on body posture shows a sitting position. Appearance and clothing Mario Teguh uses neat koko clothes. Facial expressions are smiling with attention to the audience. Hand movements are in accordance with the topic discussed. Eye gaze occasionally looks at the material and more often looks at the audience